2015
DOI: 10.1136/jnnp-2014-310148
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for being offered epilepsy surgery: 5-year experience of a tertiary referral centre: Table 1

Abstract: There was a low chance (<10%) of being offered surgery if there were bilateral lesions on MRI and extratemporal lobe epilepsy. Patients should be given advice on the risk/benefit ratio and of realistic outcomes of epilepsy surgery; this may help reduce the number of patients who refuse surgery after comprehensive workup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 8 publications
2
34
1
Order By: Relevance
“…Although Grade 1 patients predominantly underwent temporal lobectomies, it is noteworthy that of the 36 cases of unilateral MTS, 30 were classified as Grade 1, and 6 were classified as Grade 2, with a total of 19 going on to becoming seizure‐free. Patients with temporal lobe epilepsy and those with structural lesions are more likely than patients with extratemporal and nonlesional epilepsy to be considered optimal surgical candidates as supported by the literature, and reflected by the ESGS. However, it is important to acknowledge that extratemporal lesional cases have the potential to be excellent candidates for resective surgery, but may often require additional confirmation of localization.…”
Section: Discussionmentioning
confidence: 87%
“…Although Grade 1 patients predominantly underwent temporal lobectomies, it is noteworthy that of the 36 cases of unilateral MTS, 30 were classified as Grade 1, and 6 were classified as Grade 2, with a total of 19 going on to becoming seizure‐free. Patients with temporal lobe epilepsy and those with structural lesions are more likely than patients with extratemporal and nonlesional epilepsy to be considered optimal surgical candidates as supported by the literature, and reflected by the ESGS. However, it is important to acknowledge that extratemporal lesional cases have the potential to be excellent candidates for resective surgery, but may often require additional confirmation of localization.…”
Section: Discussionmentioning
confidence: 87%
“…Possible reasons are more extended information about chances and risks of surgery (as documented by the increasingly comprehensive information sheets before surgery (table 2)). Recently, the following reasons for patients to step back from surgery were reported: dissatisfaction with the predicted likelihood to become seizure free (52%), scepticism related to intracranial recordings (51%) and concerns about surgical risks (14%) 35. Another explanation might be fewer patients with a clear upfront motivation for surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study showed that some patients simply decline surgery due to costs or fear. 1 Indeed, a study performed at a tertiary epilepsy center in the United Kingdom showed that 32% of patients offered surgery declined to proceed, 6 which may indicate that some appropriate candidates are not undergoing surgery because of personal preferences and preconceived notions regarding surgery. Another reason might be poor communication and relationships between community neurologists and surgical epilepsy centers.…”
Section: Discussionmentioning
confidence: 99%